Antifungal potential of endophytic Burkholderia spp., plant extracts, and curcumin silver nanoparticles against Aspergillus spp. and Fusarium sp - Pham, Thi Thu Trang; Le, Vu Bao Trang; Sam, Hoa Mai; Nguyen, Van Phuong (Vietnam Journal of Biotechnology, 2024)
Numerous members of Aspergillus spp. and Fusarium spp. are pathogens possessing a broad spectrum of their host, including plants, animals, and humans. In this study, five endophytic Burkholderia spp., five plant extracts, and curcumin silver nanoparticles (C-AgNPs) were used to screen their antifungal activities against Aspergillus fumigatus, Aspergillus flavus, Aspergillus terreus, and Fusarium sp. ATCC 60289 (F. sp.). The results of dual assays showed that all five Burkholderia spp. strains NC119, NC148, NC160, NC166, and NC206 exhibited the antifungal activities with the percentage of inhibition (PI) ranging from 34.34% to 76.01%, in which the strain NC166 showed the strongest antifungal activity against all four studied fungi. Notably, Burkholderia spp. appeared to be effective against F. sp., with the PI greater than 50% in four out of five bacterial strains. In contrast, the results of well-diffusion assays with five plant extracts from Perilla frutescens L. (leaves, stems, roots), Piper betle L. (leaves), and Zingiber officinale Rosc. (rhizomes) had low probabilities of inhibiting F. sp. However, the bacterial strain Burkholderia metallica isolated from Perilla root showed the antifungal activities against F. sp with PI of 47.1%. In addition, the C-AgNPs performed considerable effectiveness in inhibiting the growth of all four fungi, with the highest PI of 71.17 ± 1.44% against Aspergillus terreus. These outcomes not only emphasize the potential of Burkholderia spp. and C-AgNPs as antimicrobial agents for the management of Aspergillus spp. and Fusarium spp., but also primarily rule out the antifungal possibility against F. sp. of some plant extracts, providing suggestions for future approaches in the research of these pathogenic fungi.